Advanced In-Flight Measurement Techniques - Boden, Fritz; Lawson, Nicholas; Jentink, Henk W.; Kompenhans, Jürgen (Research Topics in Aerospace, 2013)
The book presents a synopsis of the main results achieved during the 3 year EU-project "Advanced Inflight Measurement Techniques (AIM)" which applied advanced image based measurement techniques to industrial flight testing. The book is intended to be not only an overview on the AIM activities but also a guide on the application of advanced optical measurement techniques for future flight testing. Furthermore it is a useful guide for engineers in the field of experimental methods and flight testing who face the challenge of a future requirement for the development of highly accurate non-intrusive in-flight measurement techniques.    .